Aeromedical retrievals for gastrointestinal disorders in rural and remote Australia: the need for improved access to specialist advice. Issue 5 (19th May 2020) - Gardiner, Fergus W.; Bishop, Lara; McMahon, Kathryn; Nwose, Ezekiel U.; Connor, Susan; Begun, Jakob; Andrews, Jane M.
Abstract: The Royal Flying Doctor Service (RFDS) provides medical care to populations without access to traditional health‐care services. From 2014 to 2018 the RFDS conducted 6007 (≈1201/year) aeromedical retrievals for gastrointestinal (GI) disorders. More detailed research is needed to determine specific GI disorders that contributed to this caseload, and in particular inform whether the establishment of a GI specialist service is justified.